Criminal Policy Formulation on Regulation of Death Penalties for Criminal Actors - I Dewa Made Suartha (Journal of Morality and Legal Culture, 2020)
This article is encouraging this problem solving with finding and analyzing the formulation of the criminal offense criteria to punishable by death in Indonesian criminal law and reformulation of setting the criminal offender measurement that sentenced to death from the perspective of ius constituendum. The article based on normative legal research by examining primary and secondary legal materials by collecting legal-materials using a card system. The analytical approach uses legislation, concepts, and comparisons. The research analysis was present in the form of descriptive analysis with evaluative, systematic, formulating, and argumentative techniques in this article. The results of this research that conducted are the Indonesian criminal law does not regulate the criminal act criteria that punishable by death so that the execution of the death penalty results in injustice to both the perpetrator, the victim, and the community. The reformulation of Indonesian criminal law shall focus on the objectives and guidelines for the punishment of perpetrators of criminal offenses punishable by death refers to the Draft Criminal Code and the involvement of the victim and the community in their interests if in the execution of capital punishment there is a change to imprisonment or life imprisonment